Estudo da diversidade microbiana e níveis de endotoxinas em lesões endo-periodontais - Rovai, Emanuel da Silva [UNESP] (2014)
The endo-periodontal lesion is characterized by the association of endodontic and periodontal disease in the same tooth. The evolution of this lesion occurs by the presence of microorganisms with vast majority gram-negative anaerobes. Therefore this study aims to identify the microorganisms in endo-periodontal lesions by DNA-DNA checkerboard hybridization method, evaluate and compare the levels of endotoxins with clinical signs and symptoms. 10 teeth with endo-periodontal lesions in agree with the inclusion criteria were selected from patients in the ICT-UNESP, 10 endodontic and 10 periodontal samples were collected, stored and subsequently performed the laboratory assays. The results showed higher levels of endotoxin in periodontal pockets with mean and standard deviation of 39096 ± 39312. The mean and standard deviation values of endotoxins in root canals were 3240 ± 4001 (significantly lower p = 0.002). The Pearson correlation test showed moderate correlation, with p = 0.084. P. nigrescens species was associated with periodontal microflora (p = 0.0198) whereas in endodontic microbiota the species E. faecium (p = 0.0031), P. acnes (p = 0.0325), G. morbillorum (p = 0.0108) C. sputigena (p = 0.0031) and L. buccalis (p = 0.0055) were strongly correlated. The species P. intermedia, V parvula and P. endodontalis showed low correlation in endo-periodontal microflora. The study concluded that the periodontal pocket has higher levels of endotoxins in relation to the root canal. The microbiota of endo-periodontal lesions seems to be almost the same in their infections separated. The study suggests that the orange complex must play an important role in this type of infection